2008
DOI: 10.4103/0378-6323.42899
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intralesional verapamil with intralesional triamcinolone in the treatment of hypertrophic scars and keloids

Abstract: Intralesional verapamil may be a suitable alternative to triamcinolone in the treatment of hypertrophic scars and keloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 0 publications
2
62
3
Order By: Relevance
“…A single-blind, parallel-group study demonstrated that intralesional verapamil was comparable to intralesional triamcinolone acetonide in the treatment of keloids. Both were found to produce similar results (i.e., reductions of scar vascularity, pliability, height, and width) [60]. Intralesional triamcinolone achieved these effects faster but also had a greater incidence of adverse reactions than intralesional verapamil did [60].…”
Section: Methodsmentioning
confidence: 99%
“…A single-blind, parallel-group study demonstrated that intralesional verapamil was comparable to intralesional triamcinolone acetonide in the treatment of keloids. Both were found to produce similar results (i.e., reductions of scar vascularity, pliability, height, and width) [60]. Intralesional triamcinolone achieved these effects faster but also had a greater incidence of adverse reactions than intralesional verapamil did [60].…”
Section: Methodsmentioning
confidence: 99%
“…Allocation concealment was not reported in all of the eight studies (11, 16, 2025), and we judged all trials as unclear for allocation concealment. Two single-blinded trials (16, 24) were judged as high risk for blinding of participants and personnel. Complete information on the blinding processes was not shown by the left six studies (11, 20–23, 25) and we judged them at unclear risk for performance bias.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (16, 25) employed blinded observer to assess outcomes and were judged at low risk of detection bias. The left six trials (11, 2024) were judged as unclear risk due to no report on blinding of outcome assessment. Four trials (11, 16, 20, 24) were judged at high risk for incomplete outcome data because the numbers lost to follow up were high and no reasons were given for the losses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations